Strategi Rekonstruktif dalam Meningkatkan Pembelajaran Berbicara Siswa Kelas XI SMA Negeri 7 Pinrang - Rulianti Rulianti; Sitti Rabiah; Nurfathana Mazhud (JURNAL ILMIAH EDUNOMIKA, 2024)
This research is a classroom action research. The data analysis technique in this study is a quantitative description that describes the actual data and a qualitative description which is data that can be calculated resulting from the process of giving tests to students. The results of this study are based on observations made in the pre-action cycle, cycle I to cycle II which shows the implementation process and learning outcomes that are different from each cycle. The results of observations in cycle I showed that students' speaking skills still needed to be improved, while in cycle II it showed that students' speaking skills had improved from before. The student response in the first cycle of learning was still not optimal with the results of students' KKM achievement being at a percentage of 65.8% or as many as 27 students who achieved KKM, 34.1% or 15 students who did not reach KKM. In cycle II, student achievement increased rapidly with the number of students who achieved the KKM as many as 36 students with a percentage of 87.8% while those who did not reach the KKM were 5 people with a percentage of 12.1%. This result is reinforced by the KKM achievement criteria at SMA Negeri 7 Pinrang which is very good with a score range of 87-100. So it can be concluded that the application of reconstructive strategies can improve learning to speak in class XI SMA Neger 7 Pinrang. Keywords : reconstructive strategies, teaching speaking, text lectures.